IDENTIFIKASI POLA DAN NILAI INDEKS KEKERINGAN DI PROVINSI JAMBI MENGGUNAKAN KEETCH-BYRAM DROUGHT INDEX (KBDI) - Hilmy Muhammad Rosyid; Fendy Arifianto; Giarno Giarno (JURNAL GEOGRAFI, 2022)
Drought is one of the most common disasters in areas with tropical climates and has proven to have a detrimental impact on humans and plants. Drought can cause forest and land fires in many areas of Indonesia, especially in Sumatra and Kalimantan. Therefore, further research is needed on drought patterns, especially in Jambi Province. This study learns more about the pattern and trend of drought based on meteorological parameters in Jambi Province using the Keetch-Byram Drought Index (KBDI). The data used are weather parameter data, namely rainfall and daily maximum temperature at the two observation points of the Depati Parbo Meteorological Station and Muaro Jambi Climatology Station. The drought index is identical to the rainfall and temperature factors. The KBDI value is able to describe the number of hotspot events in the study area well with a correlation reaching 84%. The results of the calculation of the KBDI value show that throughout the 20-year period, the Jambi Province has a low risk of forest and land fires, except at the end of 2015 which had a moderate risk. This study is expected to provide information related to drought patterns based on the KBDI in Jambi Province.